2021
DOI: 10.3390/app11083667
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Active Control for a Helicopter with Multiple Landing Gears Equipped with Magnetorheological Dampers

Abstract: Due to their extensive use in various applications, helicopters need to be able to land in a variety of conditions. Typically, a helicopter landing gear system with skids or passive wheel-dampers is designed based on only one critical touchdown condition. Thus, this helicopter landing gear system may not perform well in different landing conditions. A landing gear system with magnetorheological (MR) dampers would be a promising candidate to solve this problem. However, a semi-active controller must be designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The results show that the performance of large magnetorheological dampers is adequate (Abdul Aziz et al, 2022). In addition, magnetorheological dampers can also be used in the field of aerospace for lunar landers and in the field of aviation for helicopters, and the final experimental results can be concluded that magnetorheological dampers have good applications in various fields (Luong et al, 2021; Wang et al, 2021). In the structural design of magnetorheological dampers, the advantages of bypassed magnetorheological dampers are higher shear stress, good damping force adjustability and the possibility of higher maximum damping force generated (Aziz and Aminossadati, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…The results show that the performance of large magnetorheological dampers is adequate (Abdul Aziz et al, 2022). In addition, magnetorheological dampers can also be used in the field of aerospace for lunar landers and in the field of aviation for helicopters, and the final experimental results can be concluded that magnetorheological dampers have good applications in various fields (Luong et al, 2021; Wang et al, 2021). In the structural design of magnetorheological dampers, the advantages of bypassed magnetorheological dampers are higher shear stress, good damping force adjustability and the possibility of higher maximum damping force generated (Aziz and Aminossadati, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Conventional energy absorption devices can only carry out optimal shock mitigation for specific working conditions. The shock mitigation performance is often unsatisfactory when the condition of shock excitation changes (Luong et al, 2021). The shock mitigation control system based on magnetorheological (MR) energy absorber (EA) has drawn great interest thanks to the advantages of low power consumption, short response time, simple structure, and continuously controllable damping force (Bai et al, 2019a(Bai et al, , 2019bDutta and Chakraborty, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was verified that the controllable MREA bumper based on a determined control method can effectively reduce the vehicle crash severity index and structural deformation in frontal collision compared with the conventional vehicle bumper. For the aircraft landing gear based on MR technology, Luong et al successively proposed a neural network controller (Luong et al, 2020a), robust adaptive controller (Luong et al, 2020b), and extended Skyhook controller (Luong et al, 2021), which effectively reduced the aircraft landing requirements and improved the landing efficiency. Mai et al (2020) designed an explicit model predictive control for the one-fourth vehicle suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately predicting the behavior of landing gear under various conditions is essential for ensuring the safety and reliability of aircraft operations [2]. Numerical modeling using computational tools has become an indispensable process in this domain, offering a cost-effective and efficient means of studying complex dynamic systems [3,4]. As aircraft technology continues to advance, there is a growing demand for more sophisticated landing gear systems that can adapt to varying landing conditions and provide precise attitude control.…”
Section: Introductionmentioning
confidence: 99%